Identification of hyaluric acid synthesis 2 (has2) and gremlin 1 (grem1) gene expressions in human cumulus cells as a biomarker for oocyte quality. - Abdul Wahab, Azantee Yazmie; Md Isa, Muhammad Lokman; Mohd Yassim, Haiyuni; Salleh, Yukmil Amru; Mat Yusof, Afzan; Abdul Razak, Redzuan Nul Hakim; Abdul Razak, Nik Fakhuruddin; Muhammad, Hussin; Mazlan, Muhammad Alif (Malaysian Society for Biochemistry and Molecular Biology (MSBMB), 2019)
Nowadays, the criteria for oocyte selection is based on morphological criteria however, it needs further improvement to select the best embryo quality. The gene expression in the cumulus cell plays important role in signaling for follicular development as well as for oocyte quality. The aim of this study is to investigate the present of HAS2 and GREM1 gene expression in the cumulus cells that can become a useful marker for oocyte quality. A preliminary study was performed on cumulus cells derived from four different patients that undergo assisted reproductive technique treatment. Cumulus cells were isolated from 4 patients and the expression of HAS2 and GREM1 was analyzed by using reverse transcriptase polymerase chain reaction (rt- PCR). The results shown that HAS2 and GREM1 were expressed in grade 3 oocytes, whereas, the genes were absent in grade 4 oocytes. This showed that the expression influenced the oocyte quality. Hence, the measurement of HAS2 and GREM1 expressions in cumulus cells would reliably useful tool for selecting competence oocytes with greater chances to be fertilized in assisted reproductive technique.